2021
DOI: 10.1002/ams2.691
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of post‐traumatic inferior vena cava thrombosis

Abstract: Background: Inferior vena cava thrombosis is a rare blunt abdominal trauma complication often associated with severe liver injury.We present two cases of inferior vena cava thrombosis due to mild liver injuries.Case Presentation: Case 1 was a 25-year-old woman taking oral contraceptives for dysmenorrhea who was injured in a motorcycle accident. Contrast-enhanced computed tomography revealed hepatic contusion of the sixth segment. At 1 week after the accident, inferior vena cava thrombosis was detected. Case 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Chakroun et al, attributed the size and the rapid development of IVC-Th in his case report to the endothelial intimal injury ( 1 ). The hepatic vein thrombosis, associated with liver injury, may extend to the inferior vena cava leading to development of IVC-Th ( 11 , 17 ). The hyper-coagulable and hypo-fibrinolytic state, associated with poly-trauma or due to any other unrelated causes, may lead the IVC-Th.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chakroun et al, attributed the size and the rapid development of IVC-Th in his case report to the endothelial intimal injury ( 1 ). The hepatic vein thrombosis, associated with liver injury, may extend to the inferior vena cava leading to development of IVC-Th ( 11 , 17 ). The hyper-coagulable and hypo-fibrinolytic state, associated with poly-trauma or due to any other unrelated causes, may lead the IVC-Th.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al, reported a successful outcome of conservative management of IVC-Th with a later insertion of an IVC filter. The authors opted for this option based on patient’s hemodynamic stability and the absence of any associated visceral organ injuries ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…No trauma abdominal contuso, as quatro causas primárias de trombose de VCI são trombose da veia hepática estendendo-se para a VCI, lesão endotelial da parede da VCI, estase do fluxo caval por compressão com sonda pericaval ou hematoma retroperitoneal e estados hipercoaguláveis e hipofibrinolíticos após trauma maior (MINAMI et al, 2021).…”
Section: Discussionunclassified
“…Alguns fatores predisponentes para trombose venosa após trauma são fratura na perna ou traumatismo craniano, manejo ventilatório por mais de 3 dias, cirurgia de grande porte, idade superior a 40 anos e lesão venosa (MINAMI et al, 2021).…”
unclassified